2016
DOI: 10.1371/journal.pntd.0004792
|View full text |Cite
|
Sign up to set email alerts
|

Over Six Thousand Trypanosoma cruzi Strains Classified into Discrete Typing Units (DTUs): Attempt at an Inventory

Abstract: Trypanosoma cruzi, the causative agent of Chagas disease, presents wide genetic diversity. Currently, six discrete typing units (DTUs), named TcI to TcVI, and a seventh one called TcBat are used for strain typing. Beyond the debate concerning this classification, this systematic review has attempted to provide an inventory by compiling the results of 137 articles that have used it. A total of 6,343 DTU identifications were analyzed according to the geographical and host origins. Ninety-one percent of the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
212
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(234 citation statements)
references
References 88 publications
15
212
0
7
Order By: Relevance
“…This DTU has been reported in domestic cycles from southern Latin-American countries [7, 29]. However, insects infected with TcV have been reported in domestic habitats in Colombia including some reports of human infections [10, 30].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This DTU has been reported in domestic cycles from southern Latin-American countries [7, 29]. However, insects infected with TcV have been reported in domestic habitats in Colombia including some reports of human infections [10, 30].…”
Section: Discussionmentioning
confidence: 72%
“…However, insects infected with TcV have been reported in domestic habitats in Colombia including some reports of human infections [10, 30]. TcV associated with sylvatic cycles has been reported with a frequency of 3.5% [29]. Consistent with our findings of TcV, a recent study [31] reported the presence of TcV in Colombian isolates obtained from P. geniculatus , R. prolixus , T. venosa and armadillos, using high-resolution markers: MLST, MLMT and ten mitochondrial markers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new clade designated Tcbat, genetically more closely related to TcI than to any other DTU, was described [73]. Some authors have recently proposed that Tcbat be recognized as an additional DTU within T. cruzi [74, 75], even though there are too few results from Tcbat to confirm or reject its validity [76]. Association of this clade with specific hosts or vectors will have to await more appropriate gene markers, since it is poorly recognized by existing techniques, and at least in the Neotropical region of Mexico, it has not been identified using the 18SrRNA (Izeta, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Phyloepidemiology and host vector associations of T. cruzi are complex, but have been partially resolved (Yeo et al 2005; Miles et al 2009; Messenger et al 2015; Brenière et al . 2016). TcI is widespread through the Americas.…”
Section: Introductionmentioning
confidence: 99%